2012
DOI: 10.5194/nhess-12-687-2012
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation extremes in the wettest Mediterranean region (Krivošije) and associated atmospheric circulation types

Abstract: Abstract. The aim of this paper is to analyse indices of extreme precipitation in Krivošije, Montenegro, the wettest Mediterranean region, from the period 1951-2007 and their relationships with atmospheric circulation using "SynopVis Grosswetterlagen" (SVG) series. Data from two stations were analysed, namely Crkvice (42 • 34 N and 18 • 39 E) and Herceg Novi (42 • 27 N and 18 • 31 E). Four indices of precipitation extremes (SDII, R75p, R95p, R95pTOT) were assessed including number of dry days. The results sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 32 publications
0
31
0
2
Order By: Relevance
“…The average annual rainfall is 2120 mm and the totals in the country generally decrease from the southwest towards the northeast. The mountains in the southwest, receiving above 4000 mm of precipitation, are the wettest part of the Mediterranean region (Ducić et al, 2012).…”
Section: Study Areamentioning
confidence: 99%
“…The average annual rainfall is 2120 mm and the totals in the country generally decrease from the southwest towards the northeast. The mountains in the southwest, receiving above 4000 mm of precipitation, are the wettest part of the Mediterranean region (Ducić et al, 2012).…”
Section: Study Areamentioning
confidence: 99%
“…Their results have shown that the frequency of heavy rainfall has generally increased [21][22][23][24][25][26]. Specifically, the analysis of rainfall and extremes in Serbia has been the subject of several studies.…”
Section: Introductionmentioning
confidence: 99%
“…Ducić et al (2012) carried out an analysis of the relationship between extreme precipitation events and synoptic circulation types in Montenegro, the wettest Mediterranean region. In their study, they used an efficiency coefficient, expressing the ratio between a relative frequency of a given circulation type in extreme precipitation events to its mean frequency for the period spanning 1951-2007.…”
Section: Synoptic Circulation Patterns That Induce Heavy Rainmentioning
confidence: 99%